Complete Genome Sequences of Nine Bacillus cereus Group Phages - Foltz, Samantha (Genome Announc, 2016)
We report the sequences of nine novel Bacillus cereus group bacteriophages: DIGNKC, Juglone, Nemo, Nigalana, NotTheCreek, Phrodo, SageFayge, Vinny, and Zuko. These bacteriophages are double-stranded DNA-containing Myoviridae isolated from soil samples using B. thuringiensis subsp. kurstaki as the host bacterium.